Exploding Offers and Buy-Now Discounts - Mark Armstrong; Jidong Zhou (Economics and Econometrics Research Institute (EERI), 2010)
A common sales tactic is for a seller to encourage a potential customer to make her purchase decision quickly. We consider a market with sequential consumer search in which firms often encourage first-time visitors to buy immediately, either by making an “exploding offer” (which permits no return once the consumer leaves) or by offering a “buy-now discount” (which makes the price paid for immediate purchase lower than the regular price). Prices often increase when these policies are used. If firms cannot commit to their sales policy, the outcome depends on whether consumer incur an intrinsic cost of returning to a firm: if there is no such return cost, it is often an equilibrium for firms to offer a uniform price to both first-time and returning visitors; if the return cost is positive, however, firms are forced to make exploding offers.
Keywords: D40; D43; D83; 330; Consumer search; oligopoly; price discrimination; high-pressure selling; exploding offers; buy-now discounts; costly recall